(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
Components deterioration in all areas reduces the level of reliability and since these cases are part of the intrinsic nature of the components in all areas, the distribution of electrical energy is no exception and it results in aging and consequently, decreases the level of reliability. Distribution network feeders play a key role in improving the reliability of the distribution system. Feeders must be inspected and maintained to improve the reliability of the distribution system to the desired level. Inspection and maintenance of feeders is costly and the budget required to perform them is limited. On the other hand, some feeders in the network are more important than others in terms of different indices and their importance should be taken into account in planning. This paper introduces a process based on inspection for quantification of MV overhead line condition and it was tried that all factors influencing the outage of distribution network integrated into one index that called Condition Index. Since the factors affecting outage can be fixed or variable over the time and also, because of preventive actions of these factor is different, so in this study, the criteria measure related to these factors are decoupled. In order to purposefully distribution of capital and human resources in inspection of distribution networks, determination of the importance of each feeder is necessary. For this purpose, Importance Index has been introduced and calculated by using Fuzzy Analytical Hierarchy Process (FAHP) method based on criteria such as length, average load and outage rate of feeders. In order to determining inspection/service rate of each feeder, ranking of feeders has been done by combination of Importance and Condition Index on the basis of decision map. Based on report of regular inspection, assets manager make decision regarding to scheduling of mid & short term maintenance. Finally, this proposed framework has been applied on the 10 feeders of one sub-transmission substation in Mashhad Electric Energy Distribution Company (MEEDC) as a case study.